Exploring the reactivity of 2-trichloromethylbenzoxazoles for access to substituted benzoxazoles - Lester, Roy P.; Bham, Travis; Bousfield, Thomas W.; Lewis, William; Camp, Jason E. (American Chemical Society, 2016)
The reactivity of 2-trichloromethylbenzoxazoles towards various nucleophiles, under metal free or iron-catalyzed conditions, for the synthesis of substituted benzoxazoles is described. These methods allow for selective substitution at either the 2- or 2’- position of the benzoxazoles using the same starting materials / reagents. This approach allows for the controlled synthesis of a variety of key derivatives from a single 2-trichloromethylbenzoxazole starting material.